2003
DOI: 10.1080/14734220309406
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory properties of cuneocerebellar neurones in the main cuneate nucleus of the rat

Abstract: Cells in the main cuneate nucleus (MCN) are known to provide a direct projection to the cerebellum, but the precise nature of the information these cells transmit to the cerebellum is unknown. The present study employed anatomical and electrophysiological procedures to determine the location of cuneocerebellar cells in the MCN, and their somatosensory properties in the rat. The location of neurones projecting to the cerebellum was determined with injections of the retrograde tracers, horseradish peroxidase or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The dorsal column nuclei are comprised of the gracile, main cuneate, and external cuneate nuclei and are thought to be the functional equivalent of the spinocerebellar tract for the upper limbs (Ekerot and Larson 1972). They carry proprioceptive and cutaneous information mainly from the upper limbs to the cerebellum (Ekerot and Larson 1972;Haring et al 1984;Cerminara et al 2003;Quy et al 2011) and also terminate heavily within the AZ and PZ (Jasmin and Courville 1987;Massopust et al 1985;Berretta et al 1991;Tolbert and Gutting 1997;Quy et al 2011;Akintunde and Eisenman 1994). Experiments performed in rats suggested that the spinocerebellar and dorsal column nuclei pathways, namely the external cuneate projections that provide the largest source of cerebellar afferents from the dorsal column nuclei, terminate into complementary bands in the AZ and PZ (Ji and Hawkes 1994;Alisky and Tolbert 1997;Quy et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The dorsal column nuclei are comprised of the gracile, main cuneate, and external cuneate nuclei and are thought to be the functional equivalent of the spinocerebellar tract for the upper limbs (Ekerot and Larson 1972). They carry proprioceptive and cutaneous information mainly from the upper limbs to the cerebellum (Ekerot and Larson 1972;Haring et al 1984;Cerminara et al 2003;Quy et al 2011) and also terminate heavily within the AZ and PZ (Jasmin and Courville 1987;Massopust et al 1985;Berretta et al 1991;Tolbert and Gutting 1997;Quy et al 2011;Akintunde and Eisenman 1994). Experiments performed in rats suggested that the spinocerebellar and dorsal column nuclei pathways, namely the external cuneate projections that provide the largest source of cerebellar afferents from the dorsal column nuclei, terminate into complementary bands in the AZ and PZ (Ji and Hawkes 1994;Alisky and Tolbert 1997;Quy et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the cat, the DCN-complex inputs are segregated in the cerebellum by their modalities, such that cutaneous and proprioceptive fibres project to superficial and deeper portions of the folia, respectively (Cerminara et al, 2003;Cooke, Larson, Oscarsson, et al, 1971;Ekerot & Larson, 1972;Rinvik & Walberg, 1975). However, proprioceptive and cutaneous inputs from Cu and ECu were found to be overlapping in the cerebellum of raccoons, suggesting that these animals do not have the same discrete modality segregation within folia (Haring & Rowinski, 1982).…”
Section: Cuneate Nucleimentioning
confidence: 98%
“…The cerebellum is also the target of ipsilateral Cu projections ( Figure 5) (Cerminara, Makarabhirom, & Rawson, 2003;Cooke, Larson, Oscaesson, et al, 1971;Cooke, Larson, Oscarsson, & Sjölund, 1971;Quy et al, 2011). Cu-cerebellar neurons are found almost exclusively in CuR, with some in the CuM shell (Haring & Rowinski, 1982), and are typically much smaller than thalamic projecting Cu neurons (Cheek, Rustioni, & Trevino, 1975;Mantle-St. John & Tracey, 1987;Rinvik & Walberg, 1975;Somana & Walberg, 1980).…”
Section: Cuneate Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…All four afferent types are classed as Aβ fibres, which are myelinated large diameter fibres with fast conduction velocities (16-100 m/s) (Abraira & Ginty, 2013). Conduction velocities are species-dependent, humans (Knibestöl, 1973), monkeys (Perl, 1968), and cats (Brown & Iggo, 1967;Burgess, Petit, & Warren, 1968) have fibres that reach the upper limits of this range, while rat Aβ fibres can conduct up to ~70 m/s (Handwerker, Kilo, & Reeh, 1991;Leem, Willis, & Chung, 1993;Sanders & Zimmermann, 1986). Slowly-adapting afferents respond best to maintained mechanical skin indentation with a characteristic sustained, slowly decreasing action potential firing rate.…”
Section: Glabrous Skinmentioning
confidence: 99%